PERCEIVED STRESS IN UNDERGRADUATE PHYSICAL THERAPY STUDENTS OF PESHAWAR, PAKISTAN - Shah, Inayat; Habib, Syed Hamid; Yousafzai, Yasar Mehmood; Ali, Asif; Ikram, Sareena; Zia, Huma; Said, Rashida (Pakistan Journal of Physiology, 2023)
Background: Stress results from different kind of stressors that affect students either positively or negatively depending on their coping ability. Academic stressors are the main cause of stress and depression among undergraduate allied health sciences’ students. The aim of this study was to determine the prevalence of perceived stress and its association with gender among undergraduate physical therapy students of Peshawar. Methodology: Level of perceived stress was assessed using cross sectional study design at different Physiotherapy institutes of Peshawar, Pakistan. A total of 300 students were recruited from five different institutes. Degree and prevalence of stress was assessed using Perceived stress scale (Cohen PSS 10). Results: Seventy-two percent students were found to be moderately stressed, 23.3% were highly stressed whereas 4.7% had low level of stress. Female students showed significantly higher stress levels (23.50 ± 4.80 vs 21.50 ± 5.60, p = 0.01). Control on irritation and confidence were considered as positive stressors whereas nervousness, stress and loss of patience were found to be the important negative stressors. Conclusion: A significant number of physiotherapy students fall in moderate to high stress categories with female preponderance.